Project tender: soil investigation Taman Tangkak Emas - Fasa 3 / Nur Atira Jamaluddin - Jamaluddin, Nur Atira (Universiti Teknologi MARA UiTM,Perak, 2022)
The case study topic that I chose was Project Tender: Soil Investigation Taman Tangkak Emas 3. The company that I practical for are included same with this report also the case study. My requirements were achieved since I was able to complete my practical training, gain experience in the operation, and complete my case study report. Throughout the project, I used the approaches by interviewing them about office management, and gathering document evaluations from the management either through face to face or online.